Energy Levels, Lifetimes, and Transition Properties for N iii – v - Meichun Li; Juan Du; Kaijian Huang; Wenxian Li (Atoms, 2025)
We present excitation energies, transition wavelengths, electric dipole (E1) transition rates, oscillator strengths, line strengths, and lifetimes for the 86 lowest states up to and including <semantics>1s22s27f</semantics> in N iii, the 125 lowest states up to and including <semantics>1s22s7f</semantics> in N iv, and the 53 lowest states up to <semantics>1s28g</semantics> in N v using the multiconfiguration Dirac–Hartree–Fock (MCDHF) and relativistic configuration interaction (RCI) methods. The computed results are then compared with data from the Atomic Spectra Database of the National Institute of Standards and Technology (NIST-ASD), experimental results, and other theoretical studies. For all levels in N iii – v, the root mean square energy differences from the NIST values are 130, 103, and 6 cm−1, respectively. Compared to previous multiconfiguration Hartree–Fock and the Breit–Pauli (MCHF-BP) calculations, 89.3%, 98.5%, and 100% of the <semantics>log(gf)</semantics> values for N iii – v agree within 5%, respectively.